Solar radiation: vitamin D and skin cancer - Nowicka, Grażyna (Studia Ecologiae et Bioethicae, 2008)
Solar radiation is a part of the environment of man. Ultraviolet В radiation in required for the biosynthesis of vitamin D, which is generally associated with calcium metabolism and significantly influences a wide range of metabolic systems, therefore, has a strong influence on human health. However, exposure to sunlight carries potential risks to human health. Ultraviolet radiation is a known carcinogen and excessive sunlight exposure significantly increases risk of skin cancer.